KABAR BENCANA DARI SURAT KABAR: MEMBACA ULANG SEJARAH BENCANA 20 MEI 1938 - Jefrianto, Jefrianto (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2022)
The earthquake and tsunami that occurred in Tomini Bay and Palu Bay, on May 20, 1938, was one of the natural disasters that attracted much attention in the archipelago at that time. This research was conducted to thoroughly review the history of the 20 May 1938 disaster, in the eyes of the newspapers published in the Dutch East Indies and the Netherlands at that time. Newspaper sources from the disaster were considered capable of presenting an overview of the atmosphere after the disaster and how the handling efforts were carried out by the Dutch East Indies government and religious and humanitarian organizations. This study used historical methods consisting of heuristics (finding sources), source criticism, interpretation (meaning), and historiography (writing history). It is hoped that the results of this study can be a learning material for people living in the Central Sulawesi region, especially Palu Bay which is crossed by the Palu Koro Fault, and Tomini Bay which is crossed by several faults, one of which is the Tokararu Fault.